Estimas mediante lavados secuenciales de la contribución de la deposición seca y lixiviación al aporte de nutrientes a un suelo forestal - López M.V.; Bellot J.; Escarré A. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
This study compares data on conductivity, pH and the enrichment factor of Ca++, Na+, K+ and Mg++ cations, coming from the sequential wash off of branches of pine, Pinus sylvestris, and holmoak, Quercus ilex, using water with a chemical composition similar to the rainfall water of the studied area. The aim the study is to quantify the importance of dry deposition and leaching in the net supplies of those ions; for this purpose, the branches were covered without being exposed to external deposition processes for a certain period of time, while others were kept under natural conditions.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)